Guidelines for technogenic landform mapping in the Brazilian Relief Classification System (BRCS) - Moura, Nina Simone Vilaverde; Da Silva, Telma Mendes; Gouveia, Isabel Cristina Moroz-Caccia [UNESP]; De Oliveira Peixoto, Maria Naíse; Felippe, Miguel Fernandes; Dos Santos Oliveira, Antônio Manoel; Peloggia, Alex Ubiratan Goossens; Nolasco, Marjorie Cseko (My University, 2023)
The objective of this work is to discuss the particularity of the classification of technogenic landforms, that is, directly or indirectly derived from human agency, through the studies carried out within the scope of the Brazilian Relief Classification System. Such forms, as an expression of technogenic grounds, are analyzed through the morphostratigraphic, based on their formation processes, configuration, and constituent materials. Such application led to the following results in terms of classification, into two basic levels: (1) Categories, defined according to the geomorphological dynamics, whether additive (elevations or superpositions), subtractive (scars or depressions) or conservative (corrugations and equiforms), the latter differentiated by the occurrence or not of topographic alteration; (2) Types, differentiated according to human agency, whether direct (technoforms) or indirect (geotechnoforms) or even according to the superficial or deep nature of the modifying process (in the case of equiforms). It is concluded that technogenic forms constitute a particular geomorphological category, subject to analysis, classification and mapping using specific methods, and their taxonomic reference is considered in a cross-sectional approach, observing their expression at the level of the sixth, fifth and fourth taxa of Ross (1992); variations in this classification may occur in view of the dimensions of the landscape or classified form.
Diretrizes para mapeamento de formas de relevo tecnogênicas no Sistema Brasileiro de Classificação do Relevo (SBCR)
Keywords: anthropic alterations; geomorphological mapping; technogenic relief patterns